PEMANFAATAN LIMBAH PERTANIAN TANAMAN PANGAN DAN HIJAUAN PAKAN TERNAK RUMINANSIA DI KECAMATAN WAEAPO KABUPATEN BURU - Basyari, Arif; Eoh, Marna; Patty, Christian W. (JURNAL HUTAN PULAU-PULAU KECIL, 2024)
This research aims to determine the presentation of the use of agricultural food crop waste as ruminant animal feed, the presentation of the use of forage as ruminant animal feed, to determine the extent of the application of agricultural waste processing technology and techniques for using agricultural waste by respondents. This research uses a survey method by conducting interviews with respondents and field observations at the research location. The sampling technique was carried out using purposive sampling, namely three villages were taken (Wanareja, Waenetat and Waekasar Villages) based on the largest number of respondent farmers and 30 respondents were taken. The results of the research show that in Waeapo District the use of agricultural food crop waste (rice straw) as ruminant feed is 53% (16 respondents) and the use of hay as animal feed, as well as the use of forage as ruminant feed is 47% (14 respondents) while field grass and food crop agricultural waste amounted to 53% (16 respondents) which provided field grass and superior grass. There are 53% (16 respondents) who have implemented feed processing technology from agricultural waste in the form of hay.